Anatomical variations of the hepatobiliary system in Sudanese patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) - Doush, Wael; A-Galil, Mohammed; Ibrahim, Shakir (International Journal of Medicine, 2017)
Background: The meticulous identification of the hepatobiliary tree system normal anatomy during surgical operations is crucial in iatrogenic injury prevention. Equally important, an understanding of the congenital variations of biliary and vascular anatomy, as the literature abounds with reports of specific anatomical variations, and their surgical implications.Aim: This study aimed to study the presence of anatomical variations within the hepatobiliary system in Sudanese population undergoing endoscopic retrograde cholangiopancreatography (ERCP).Patients and methods: The records of patients undergoing ERCP in Soba University Hospital during 2004 to 2008 were analyzed. There were 277 Sudanese patients who had complained of right hypochondrial abdominal pain & history of jaundice (obstructive jaundice) that underwent ERCP were included within this study. The exclusion criteria included the following: Sudanese patients in whom ERCP failed or patients who had advanced hepatobiliary disease like cancers, strictures either cancerous or iatrogenic, fistula and iatrogenic biliary leak.Results: The analysis of 277 Sudanese patients undergoing ERCP of the hepatobiliary system showed the following results regarding the variations: The choledochal cyst type one (fusiform type) was present in 3 (1.08%) patients; very low cystic duct insertion (parallel) was present in 1 (0.36%) patient and long cystic duct was present in 3 (1.08%) patients. The ampulla of Vater size variations occurred as A) Normal in 158 (57%) patient, B) Small in 56 (20.2%) patients, C) Large in 29 (10.5%) patients, D) Periampullary diverticula in 4 (1.4%) patients and E) unclassified in 30 (10.8%) patients. Other forms of congenital anomalies were not found.Conclusion: The using of endoscopic retrograde cholangiopancreatography (ERCP) is a reliable radiological method for depicting congenital anomalies of the hepatobiliary system, but it is an invasive procedure.